CNS midline cells are required for establishment and differentiation of Drosophila MP2 interneurons. - Kim, I.O.; Jeon, S.H.; Kim, S.H. (Biochemical and Biophysical Research Communications, 2007)
The Drosophila CNS develops from the ventral neuroectoderm (VNE) on both sides of the midline along the dorsoventral axis. During early neurogenesis, three homeodomain and Egfr signaling genes are required for the dorsoventral patterning of the VNE. However, the roles of CNS midline cells in patterning of the specific neural lineages are not well understood. Their roles in identity determination and differentiation of the well-established MP2 lineage were studied using several molecular markers. We showed that these cells are essential for identity determination of the MP2 lineage that originates from the VNE. The midline cells and the Egfr signaling genes were also required for the proper maintenance of MP2 and the correct formation of MP2 axonal pathways. Overexpression of sim in the midline cells activated ectopic expression of MP2 markers in the VNE. This analysis suggests that CNS midline cells and Egfr signaling genes play essential roles in the proper establishment and differentiation of the MP2 lineage.